If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9 = 5 + h Solving -9 = 5 + h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-1h' to each side of the equation. -9 + -1h = 5 + h + -1h Combine like terms: h + -1h = 0 -9 + -1h = 5 + 0 -9 + -1h = 5 Add '9' to each side of the equation. -9 + 9 + -1h = 5 + 9 Combine like terms: -9 + 9 = 0 0 + -1h = 5 + 9 -1h = 5 + 9 Combine like terms: 5 + 9 = 14 -1h = 14 Divide each side by '-1'. h = -14 Simplifying h = -14
| -6.5+4x-7= | | -3y=1.17 | | 73.00-7.33= | | 2(m+4)=16 | | -2x+0=-x+2 | | 11x^2+14x+3= | | 73.00-.33= | | 6x-(-40)=22 | | 12=-3y | | 38x+(4x*2)=3000 | | 2x+7=6x+1 | | 2x+28=6x+56 | | 3(x-7.7)=9.9 | | -2px-x+2=0 | | 13=4-3g | | 2/9n=-6 | | 2/9xn=-6 | | -2px-2+2=0 | | (17-x)/23=-25 | | 8c-5=-197 | | 4x+11y=5 | | 65=6t+8 | | 147=-3x-6(-2x-11) | | 5x+7.34=3x+11 | | (9.5x-75)/(X-15)=9.75 | | n(n^2-1)(n-2)=720 | | 1=5-q | | 9y+4=-239 | | 0=9n-n | | 1/6x10-23g | | 4006=5k+6 | | 2h-2=12 |